HSP: Bystander Antigen in Atopic Diseases? - Aalberse, Joost A.; Kapitein, Berber; Prakken, Berent J. (Frontiers in Immunology, 2012)
Over the last years insight in the complex interactions between innate and adaptive immunity in the regulation of an inflammatory response has increased enormously. This has revived the interest in stress proteins; proteins that are expressed during cell stress. As these proteins can attract and trigger an immunological response they can act as important mediators in this interaction. In this respect, of special interest are proteins that may act as modulators of both innate and adaptive immunity. Heat shock proteins (HSPs) are stress proteins that have these, and more, characteristics. More than two decades of studies on HSPs has revealed that they are part of intrinsic, “natural” mechanisms that steer inflammation. This has provoked comprehensive explorations of the role of HSPs in various human inflammatory diseases. Most studies have focused on classical autoimmune diseases. This has led to the development of clinical studies with HSPs that have shown promise in Phase II/III clinical trials. Remarkably, only very little is yet known of the role of HSPs in atopic diseases. In allergic disease a number of studies have investigated the possibility that allergen-specific regulatory T cell (Treg) function is defective in individuals with allergic diseases. This raises the question whether methods can be identified to improve the Treg repertoire. Studies from other inflammatory diseases have suggested HSPs may have such a beneficial effect on the T cell repertoire. Based on the immune mechanisms of atopic diseases, in this review we will argue that, as in other human inflammatory conditions, understanding immunity to HSPs is likely also relevant for atopic diseases. Specifically, we will discuss why certain HSPs such as HSP60 connect the immune response to environmental antigens with regulation of the inflammatory response. Thus they provide a molecular link that may eventually even help to better understand the immune pathological basis of the hygiene hypothesis.